Retrospective comparison between the Prolift and Elevate anterior vaginal mesh procedures: 18-month clinical outcome. Issue 12 (December 2015) - Rogowski, Artur; Bienkowski, Przemyslaw; Tarwacki, Dariusz; Szafarowska, Monika; Samochowiec, Jerzy; Sienkiewicz-Jarosz, Halina; Jerzak, Malgorzata; Baranowski, Wlodzimierz
Abstract Introduction and hypothesis There are few direct comparisons between the first-generation trocar-guided and the second-generation single-incision mesh systems in the treatment of anterior pelvic organ prolapse (POP). Hence, the purpose of this retrospective review was to compare 18-month operative success in female patients who had undergone POP surgery with the anterior Prolift (n  = 52) or the anterior Elevate mesh (n  = 62). Methods Subjective (bulge symptoms) and objective measures (absence of anterior or apical descent beyond the hymen, POP-Q anterior stage 0 or I, no retreatment for POP) were used as the measures of surgical efficacy. Postoperative pelvic floor pain, dyspareunia, de novo overactive bladder (OAB), de novo stress urinary incontinence (SUI), and mesh exposure were addressed as complications of POP surgery. Results The two groups did not differ with regard to the subjective and objective measures of the operative efficacy. There were no between-group differences in the proportion of women reporting postoperative pelvic floor pain, dyspareunia, de novo SUI, and de novo OAB symptoms (allp values >0.05). The proportion of patients with postoperative vaginal exposure was significantly higher in the Prolift group (7.7 %) than in the Elevate group (0.0 %;p  = 0.02). Conclusions In conclusion, our results suggest that the use of the Elevate system in patients with anterior compartment prolapse results in fewer mesh erosions, but similar efficacy, compared with the Prolift mesh.